Service Delivery Reviews in Canada and the U.K. - World Bank (Washington, DC, 2012)
This brief describes in detail Canada's policy on alternative service delivery and service delivery reviews in the UK, such as the prior options reviews, better quality services and best value reviews, market testing, and fundamental expenditure reviews. Links are provided to relevant documents and case studies.